Elevated levels of 14-3-3 proteins, serotonin, gamma enolase and pyruvate kinase identified in clinical samples from patients diagnosed with colorectal cancer - Dowling, Paul; Hughes, David J; Larkin, Anne Marie; Meiller, Justine; Henry, Michael; Meleady, Paula; Lynch, Vincent; Pardini, Barbara; Naccarati, Alessio; Levy, Miroslav; Vodicka, Pavel; Neary, Paul; et al. (Clinica chimica acta, 2015)
BACKGROUND: Colorectal cancer (CRC), a heterogeneous disease that is common in both men and women, continues to be one of the predominant cancers worldwide. Lifestyle, diet, environmental factors and gene defects all contribute towards CRC development risk. Therefore, the identification of novel biomarkers to aid in the management of CRC is crucial. The aim of the present study was to identify candidate biomarkers for CRC, and to develop a better understanding of their role in tumourogenesis. METHODS: In this study, both plasma and tissue samples from patients diagnosed with CRC, together with non-malignant and normal controls were examined using mass spectrometry based proteomics and metabolomics approaches. RESULTS: It was established that the level of several biomolecules, including serotonin, gamma enolase, pyruvate kinase and members of the 14-3-3 family of proteins, showed statistically significant changes when comparing malignant versus non-malignant patient samples, with a distinct pattern emerging mirroring cancer cell energy production. CONCLUSION: The diagnosis and management of CRC could be enhanced by the discovery and validation of new candidate biomarkers, as found in this study, aimed at facilitating early detection and/or patient stratification together with providing information on the complex behaviour of cancer cells.
Keywords: lidé středního věku; Colorectal Neoplasms; fosfopyruváthydratasa; metabolomika; Proteomics; Male; lidé; kolorektální nádory; hmotnostní spektrometrie; senioři; proteiny 14-3-3; Aged; Phosphopyruvate Hydratase; 14-3-3 Proteins; ženské pohlaví; Metabolomics; Pyruvate Kinase; Serotonin; serotonin; mužské pohlaví; Middle Aged; Humans; pyruvátkinasa; proteomika; Mass Spectrometry; Female